2014
DOI: 10.1016/j.semarthrit.2014.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Chronic arthritis and cardiovascular disease: Altered blood parameters give rise to a prothrombotic propensity

Abstract: This analysis provides a first identification of the mechanisms by which inflammatory arthritis can aggravate cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 99 publications
1
27
0
4
Order By: Relevance
“…Several studies have demonstrated that TNF-α inhibits activation of protein C, thereby affecting the coagulation process [6870]. …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that TNF-α inhibits activation of protein C, thereby affecting the coagulation process [6870]. …”
Section: Discussionmentioning
confidence: 99%
“…Carotid intima media thickness, endothelial dysfunction, MPV and EAT thickness are some parameters that suggested for evaluation of increased atherosclerotic risk [3-5,7]. Familial Mediterranean fever is an inflammatory disease suggested to predispose to atherosclerosis [4-6].…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of atherosclerosis was reported to be increased in cases with rheumatic diseases [1,3]. Case-control studies allowing evaluation of carotid intima media thickness and endothelial dysfunction found a predisposition of FMF patients to atherosclerosis [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…84 This review did not focus on clinical endpoints, but instead subclinical measures, which can provide mechanistic insight. Thus, our results do not mean that anti-TNFα treatment could not result in an improvement in outcomes due to other mechanisms; for example, a reduction in prothrombotic tendency 85,86 or through improvement in quality of life facilitating lifestyle change. Furthermore, this study only addresses anti-TNFα biologics.…”
Section: Antibody Associated Systemic Vasculitismentioning
confidence: 59%